Strong Intermolecular Exciton Couplings in Solid‐State Circular Dichroism of Aryl Benzyl Sulfoxides. Issue 9 (11th December 2013) - Padula, Daniele; Pietro, Sebastiano Di; Annunziata, Maria; Capozzi, M.; Cardellicchio, Cosimo; Pescitelli, Gennaro
ABSTRACT A series of 13 enantiopure aryl benzyl sulfoxides (1a, 1b, 1c, 1d, 1e, 1f, 1g, 1h, 1i, 1j, 1k, 1l, 1m) with different substituents on the two aromatic rings has been previously analyzed by means of electronic circular dichroism (CD) spectroscopy. Most of these compounds are crystalline and their X‐ray structure is established. For almost one‐half of the series, CD spectra measured in the solid state were quite different from those in acetonitrile solution. We demonstrate that the difference is due to strong exciton couplings between molecules packed closely together in the crystal. The computational approach consists of time‐dependent density functional theory (TDDFT) calculations run on "dimers" composed of nearest neighbors found in the lattice. Solid‐state CD spectra are well reproduced by the average of all possible pairwise terms. The relation between the crystal space group and conformation, and the appearance of solid‐state CD spectra, is also discussed. Chirality 26:102–110, 2013. © 2013 Wiley Periodicals, Inc.